Willingness to Pay for Dental Fear Treatment. Is Supplying Fear Treatment Socially Beneficial? - Bente Halvorsen; Tiril Willumsen (Statistics Norway, Research Department, 2002)
The aim of this paper is to discuss the social desirability of a treatment program for patients with dental fear. The program consisted of three different fear treatments, cognitive therapy, applied relaxation or nitrous oxide sedation, as well as dental treatment. To evaluate the effects of uncertainty on the patients' benefits from the program, we elicit their willingness to pay both before and after receiving treatment, since we expected patients to be uncertain about the outcome of the fear treatment. We find that the social desirability of the treatment is very sensitive towards uncertainty. While only 24 percent of the patients were willing to pay the actual cost of the treatment before attending, 71 percent were willing to pay afterwards. This implies that many patients who would benefit from the treatment ex post are not willing to pay the cost of the treatment ex ante, and will thus not receive any treatment unless it is subsidised.
Keywords: I11; D61; 330; Dental fear treatment; willingness to pay.